Preparation method and application of high-performance and environment-friendly aluminum sol coating

CN122898166APending Publication Date: 2026-10-13CHIZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610946127.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-29
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0003]然而,现有铝溶胶涂层技术仍存在以下不足:其一,涂层与金属、玻璃等基材之间的界面附着力普遍偏低,尤其是在湿热、盐雾等苛刻环境下易发生剥离失效

Benefits of technology

[0040]1. 本发明通过构建仿生配位催化过渡层、双源D80催化、两步梯度热固化的多重协同体系,显著提升了铝溶胶涂层的界面结合力、交联致密性与多功能集成能力。首先,在基材表面原位形成的单宁酸-Fe3+动态配位网络,利用邻苯三酚基团对金属氧化物的强配位锚定作用,结合KH550的共价键合与D80的界面催化,使预处理层从传统的被动粘附转变为兼具锚定、反应与催化功能的活性过渡层;在此基础上,涂层本体中再次引入D80与ε-聚赖氨酸,并采用95~125℃的两步梯度固化,促使PEG诱导的微相分离形成稳定的微纳粗糙疏水结构,同时实现铝溶胶与有机硅网络的深度互穿。由此获得的涂层附着力最高可达5B级,接触角超过118°,热分解温度提升至298℃以上,且对大肠杆菌和金黄色葡萄球菌的抑菌率均高于99%,综合性能显著优于现有技术。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898166A_ABST
    Figure CN122898166A_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of environmental protection coating, and particularly relates to a preparation method of high-performance and environmentally-friendly aluminum sol coating and application thereof. The present application significantly improves the interface bonding force, cross-linking compactness and multi-functional integration capability of the aluminum sol coating by constructing a multi-synergistic system of biomimetic coordination catalytic transition layer, double-source D80 catalysis and two-step gradient thermal curing. The pretreatment working liquid and coating sol of the present application are both mainly water-based solvents, all raw materials are cheap and easy to obtain, and the coating and curing process does not require special equipment, which can be directly compatible with the existing coating production line. In the post-treatment step, the tannic acid in the coating is used to anchor ZnO nanoparticles in situ, without the need for additional adhesives, which endows the coating with ultraviolet light catalytic self-cleaning ability without damaging the original structure and antibacterial property. The corrosion area is only 1.2% after 500h of salt spray test, indicating that the coating has long-term protection capability in harsh environments such as automobiles, ships and building glass, and has clear engineering application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of environmentally friendly coating technology, specifically relating to a method for preparing a high-performance, environmentally friendly aluminum sol coating and its application. Background Technology

[0002] Aluminum sol coatings are a class of functional coating materials using nano-alumina particles as inorganic precursors. Due to their excellent corrosion resistance, wear resistance, high-temperature resistance, and chemical stability, they have been widely used in automotive manufacturing, ship protection, building decoration, aerospace, and electronic packaging. In recent years, with increasingly stringent environmental regulations, environmentally friendly aluminum sol systems using water as a solvent have gradually replaced traditional organic solvent systems, becoming a research hotspot. To further improve the overall performance of aluminum sol coatings, researchers have attempted to introduce organosilicon sol-gel components (such as methyltrimethoxysilane) to construct organic-inorganic composite networks, or add organometallic catalysts such as dibutyltin dilaurate (D80) to promote cross-linking reactions and improve the coating's density and mechanical properties.

[0003] However, existing aluminosilicate coating technologies still have the following shortcomings: First, the interfacial adhesion between the coating and substrates such as metals and glass is generally low, especially in harsh environments such as humidity, heat, and salt spray, where peeling failure is prone to occur. Although conventional silane coupling agent pretreatment can improve interfacial bonding to some extent, the resulting monolayer lacks catalytic activity and cannot form a gradient transition layer with chemical bonds to subsequent coatings. The cross-linking density in the interfacial region is insufficient, remaining a weak point. Second, catalysts such as D80 are usually added directly to the coating body and uniformly dispersed throughout the coating. Their effective concentration in the interfacial region is low, and the catalytic efficiency is not fully utilized. Moreover, achieving the ideal cross-linking effect often requires a high dosage, increasing costs and potential environmental risks. Third, existing aluminosilicate coatings have relatively limited functions, mostly focusing only on corrosion resistance or hydrophobic properties, making it difficult to simultaneously meet the multifunctional requirements of antibacterial and self-cleaning properties. Furthermore, post-treatment steps often require additional adhesives or complex processes. Fourth, some pretreatment processes (such as chromate passivation and phosphating) or solvent-based systems have heavy metal pollution or volatile organic compound emissions, which do not meet the requirements of green manufacturing and sustainable development.

[0004] Therefore, developing a method for preparing aluminum sol coatings that combines high adhesion, excellent thermal stability, antibacterial and self-cleaning functions with environmentally friendly and low-cost processes has significant industrial value and practical implications. Summary of the Invention

[0005] The purpose of this invention is to address existing problems by providing a method for preparing high-performance, environmentally friendly aluminum sol coatings and their applications.

[0006] This invention is achieved through the following technical solution:

[0007] A method for preparing a high-performance, environmentally friendly aluminum sol coating includes the following steps:

[0008] S1. Substrate pretreatment:

[0009] Immerse the degreased and cleaned substrate (metal, glass or ceramic) in the pretreatment working solution at room temperature for 5-10 minutes, then remove it and dry it at 60-80℃ for 5-8 minutes to form a catalytically active transition layer with a thickness of 20-60 nm on the substrate surface.

[0010] S2. Preparation of basic sol:

[0011] Polyvinyl alcohol and polyethylene glycol were dissolved in deionized water and stirred at 90°C until completely dissolved. After cooling to room temperature, anhydrous ethanol, neutral aluminum sol, and methyltrimethoxysilane were added in sequence and stirred at room temperature to obtain the basic sol.

[0012] S3, Addition of catalytic and antibacterial components:

[0013] Add tannic acid (pre-dissolved in a small amount of deionized water, concentration about 10wt%) to the basic sol, controlling the addition rate to ≤2mL / min, while stirring at medium speed (300~500rpm). After the addition is complete, add dibutyltin dilaurate and ε-polylysine, and stir evenly at room temperature to obtain a composite sol. Maintain the pH of the system at 5.0~5.5.

[0014] The phenolic hydroxyl groups of tannic acid react with Al in aluminum sol 3+ It has a coordination tendency, and the coordination reaction rate is moderate under weakly acidic conditions (pH 5.0~5.5); slow addition and controlled stirring can prevent local gelation and ensure sol stability.

[0015] S4. Aging and Coating:

[0016] The composite sol is aged and then coated onto the surface of the pretreated substrate.

[0017] The wet film thickness is 20~30μm;

[0018] S5, Two-step gradient thermosetting:

[0019] The thermosetting process is carried out in two stages.

[0020] Further, the raw materials, by weight, are: 15 parts neutral aluminum sol, 2.8-3.2 parts methyltrimethoxysilane (MTMS), 0.4-0.6 parts polyvinyl alcohol (PVA-1788, degree of hydrolysis 87-89%), 0.15-0.25 parts polyethylene glycol (PEG-2000), 0.15-0.25 parts tannic acid (TA), 0.08-0.12 parts dibutyltin dilaurate (D80), 0.05-0.15 parts ε-polylysine (ε-PL, molecular weight 3500-4500), 9-11 parts anhydrous ethanol, and 25-27 parts deionized water.

[0021] Furthermore, it also includes S6, post-treatment: a zinc ion-containing precursor solution is sprayed onto the cured coating surface, and in-situ anchoring is achieved by utilizing the coordination effect of the phenolic hydroxyl groups of tannic acid in the coating with zinc ions. After drying at 70~80℃ for 15~20min, zinc oxide nanoparticles are generated in-situ on the coating surface, forming a photocatalytic self-cleaning functional layer.

[0022] Furthermore, the zinc ions in the precursor solution are derived from zinc acetate or zinc nitrate, with a zinc ion concentration of 0.10~0.20 mol / L, and the solvent is a water-ethanol mixture (ethanol:water = 1:(1~3), v / v), with a solution pH of 6.0~6.5.

[0023] Furthermore, the zinc ion spraying amount is 0.3~0.4 mg Zn / cm³. 2 After spraying, let it stand at room temperature for 8-10 minutes before drying.

[0024] Furthermore, the preparation of the pretreatment working solution in step S1 includes the following steps:

[0025] (1) Dissolve tannic acid (0.8~1.2 g / L) in deionized water, and add Fe 3+ Salt (Fe) 3+ Concentration of 0.03~0.08 g / L, tannic acid: Fe 3+ The molar ratio is (3~4):1), and the mixture is stirred for 1~2 min to form a purple coordination complex;

[0026] (2) Add γ-aminopropyltriethoxysilane (KH550, 2.0~3.0 g / L) and hydrolyze for 10 min; add dibutyltin dilaurate (D80, 0.10~0.20 g / L) and stir for 5 min;

[0027] (3) Adjust the pH to 5.0~5.5 and age for 15~30 minutes.

[0028] The pretreated substrate should be coated within 1 hour to avoid secondary contamination.

[0029] Furthermore, the Fe3+ The salt is one or more of ferric chloride (FeCl3·6H2O), ferric nitrate (Fe(NO3)3·9H2O), or ferric sulfate (Fe2(SO4)3).

[0030] Furthermore, the neutral aluminum sol described in step S2 has a solid content of 20% and a pH value of 5.0~5.5.

[0031] Furthermore, the thermosetting treatment in step S5 specifically includes:

[0032] The first stage involves constant temperature curing at 95~105℃ for 0.8~1.2 hours;

[0033] As the solvent slowly evaporates, PEG segregates to the surface, inducing microphase separation between the hydrophilic phase of PVA / aluminum sol and the hydrophobic phase of polymethylsiloxane, spontaneously forming a micro-nano rough structure prototype.

[0034] The second stage involves constant temperature curing at 115~125℃ for 0.4~0.6 hours;

[0035] Silane undergoes further polycondensation, and aluminum sol forms an interpenetrating network with the organic phase, resulting in complete densification of the coating and fixation of the rough structure.

[0036] There is no ultraviolet light exposure throughout the process to avoid photo-induced hydrophilic transformation.

[0037] The aluminum sol coating prepared by the method.

[0038] The aluminum sol coating is used in self-cleaning glass for buildings, dustproofing for photovoltaic panels, automotive coatings, anti-corrosion for ships, antibacterial protection for medical devices, and moisture protection for electronic components.

[0039] The present invention has the following advantages over the prior art:

[0040] 1. This invention significantly improves the interfacial bonding strength, cross-linking density, and multifunctional integration capability of aluminum sol coatings by constructing a biomimetic coordination catalytic transition layer, dual-source D80 catalysis, and a two-step gradient thermosetting multi-synergistic system. Firstly, tannic acid-Fe2+ is formed in situ on the substrate surface... 3+A dynamic coordination network utilizes the strong coordination and anchoring effect of pyrogallol groups on metal oxides, combined with the covalent bonding of KH550 and the interfacial catalysis of D80, to transform the pretreatment layer from a traditional passive adhesion layer into an active transition layer with anchoring, reaction, and catalytic functions. Based on this, D80 and ε-polylysine are introduced again into the coating bulk, and a two-step gradient curing process (95-125℃) is employed to promote PEG-induced microphase separation, forming a stable micro / nano rough hydrophobic structure, while simultaneously achieving deep interpenetration between the aluminum sol and the organosilicon network. The resulting coating exhibits adhesion up to grade 5B, a contact angle exceeding 118°, and a thermal decomposition temperature exceeding 298℃. Furthermore, it demonstrates an antibacterial rate of over 99% against both *Escherichia coli* and *Staphylococcus aureus*, significantly outperforming existing technologies in overall performance.

[0041] 2. The pretreatment working solution and coating sol of this invention both use water as the main solvent, are free of chromium, phosphorus, and heavy metal pollution, and the components such as tannic acid and ε-polylysine are naturally biodegradable, making wastewater treatment simple. All raw materials are inexpensive and readily available. Pretreatment only requires immersion at room temperature for 5-10 minutes, and the coating and curing processes require no special equipment, making them directly compatible with existing coating production lines. In the post-treatment step, the tannic acid in the coating is used to anchor ZnO nanoparticles in situ, eliminating the need for additional adhesives and giving the coating UV photocatalytic self-cleaning ability without damaging the original structure and antibacterial properties. After 500 hours of salt spray testing, the corrosion area was as low as 1.2%, indicating that the coating has long-term protective capabilities in harsh environments such as automobiles, ships, architectural glass, medical devices, and electronic packaging. It combines high performance, multifunctionality, and green manufacturing characteristics, demonstrating clear engineering application value. Attached Figure Description

[0042] Figure 1 The results show the comparison of the antibacterial properties of the aluminum sol coatings in each embodiment and comparative example;

[0043] Figure 2 The results show the comparison of salt spray resistance of aluminum sol coatings in various embodiments and comparative examples. Detailed Implementation

[0044] Experimental materials

[0045] Table 1 Raw Materials and Manufacturers

[0046] Polyvinyl alcohol (PVA-1788) Analytical grade, degree of alcoholysis 88% Aladdin Polyethylene glycol (PEG-2000) Analytical grade, molecular weight 2000 Sinopharm Group Aluminum sol (Al-sol) LIG-I type, solid content 20%. Shandong Longli Biotechnology Co., Ltd. Methyltrimethoxysilane (MTMS) Analytical grade, purity ≥ 98%. Shanghai Chenhua Instrument Co., Ltd. Dibutyltin dilaurate (D80) Analytical grade, tin content 19.2%. Aladdin Anhydrous ethanol (EA) Analytical grade, purity ≥ 99.7% Shanghai Lingfeng Chemical Reagent Co., Ltd. Deionized water (DIW) Resistivity ≥ 18 MΩ·cm Laboratory Milli-Q system preparation Methyltrimethoxysilane (MTMS) Analytical grade, purity ≥ 98%. Aladdin Tannic acid (TA) Analytical grade, purity ≥ 98%. Aladdin γ-aminopropyltriethoxysilane (KH550) Analytical grade, purity ≥ 98%. Aladdin ε-Polylysine (ε-PL) Analytical grade, molecular weight 3500~4500 Commercially available (food grade / reagent grade)

[0047] Unless otherwise specified, the raw materials used in this invention are all from commercially available conventional products.

[0048] Experimental equipment and instruments

[0049] Table 2 Experimental Equipment and Manufacturers

[0050] Electronic balance YP-202N Measuring range 0-200g, accuracy 0.001g Thermostatic magnetic stirrer DF-101S Rotation speed 0-2000rpm, temperature control accuracy ±1℃ Electric constant temperature drying oven DHG-9070A Temperature range RT-300℃, uniformity ±2℃ Thermogravimetric analyzer (TGA) HTG-4 Heating rate: 0.1-100 K / min, accuracy: ±0.1% Contact angle measuring instrument OCA20 Measurement accuracy ±0.1°, high-speed camera 500 fps

[0051] Unless otherwise specified, the equipment used in this invention is a conventional product.

[0052] To further explain the present invention, the following specific embodiments are described.

[0053] Example 1

[0054] A method for preparing a high-performance, environmentally friendly aluminum sol coating includes the following steps:

[0055] S1. Substrate pretreatment:

[0056] After degreasing with acetone and rinsing with deionized water, the 6061 aluminum alloy plate (5cm×5cm×0.2cm) is immersed in the pretreatment working solution and soaked at room temperature for 5 minutes. After being taken out, it is dried at 60℃ for 8 minutes to form a catalytically active transition layer on the surface of the substrate.

[0057] The pretreatment working solution is prepared by dissolving 0.8 g / L of tannic acid in deionized water and adding 0.17 g / L of FeCl3·6H2O (Fe 3+ The concentration is 0.035 g / L, tannic acid: Fe 3+ The molar ratio of the two components was 3.2:1, and the mixture was stirred to form a purple coordination complex. Then, 2.0 g / L KH550 was added and hydrolyzed for 10 min. 0.10 g / L D80 was added and stirred for 5 min. The pH was adjusted to 5.0 with 0.1 mol / L dilute hydrochloric acid and aged for 15 min.

[0058] The pretreated substrate should be coated within 1 hour to avoid secondary contamination.

[0059] S2. Preparation of basic sol:

[0060] Dissolve 0.4 parts of polyvinyl alcohol and 0.15 parts of polyethylene glycol in 25 parts of deionized water, stir at 90°C until completely dissolved, cool to room temperature, and then add 9 parts of anhydrous ethanol, 15 parts of neutral aluminum sol (solid content of 20%, pH value of 5.0) and 2.8 parts of methyltrimethoxysilane in sequence, and stir at room temperature to obtain the basic sol.

[0061] S3, Addition of catalytic and antibacterial components:

[0062] Add 1.5 parts of tannic acid (10wt%) (containing 0.15 parts of tannic acid) to the base sol at a rate of 1 mL / min while stirring at a medium speed of 300 rpm. After the addition is complete, add 0.08 parts of dibutyltin dilaurate and 0.05 parts of ε-polylysine (molecular weight 3500). Stir at room temperature until homogeneous to obtain a composite sol. Maintain the pH of the system at 5.0.

[0063] S4. Aging and Coating:

[0064] After aging the composite sol for 2 hours, it was coated onto the surface of the pretreated aluminum alloy plate using a dip coating method (speed 10 cm / min), with a wet film thickness of 20 μm.

[0065] S5, Two-step gradient thermosetting:

[0066] The first stage involves curing at a constant temperature of 95℃ for 1.2 hours;

[0067] The second stage involves curing at a constant temperature of 115℃ for 0.6 hours.

[0068] No ultraviolet light exposure throughout the process to avoid photo-induced hydrophilic conversion;

[0069] S6. Post-processing:

[0070] A zinc ion-containing precursor solution is sprayed onto the cured coating surface. The phenolic hydroxyl groups of tannic acid in the coating are used to anchor the zinc ions in situ. After drying at 70°C for 20 minutes, zinc oxide nanoparticles are generated in situ on the coating surface, forming a photocatalytic self-cleaning functional layer.

[0071] The zinc ions in the precursor solution are derived from zinc acetate, with a zinc ion concentration of 0.10 mol / L. The solvent is a water-ethanol mixture (ethanol:water = 1:1, v / v), and the solution pH is 6.0.

[0072] The amount of zinc ions sprayed is 0.3 mg Zn / cm³. 2 After spraying, let it stand at room temperature for 8 minutes before drying.

[0073] Example 2

[0074] A method for preparing a high-performance, environmentally friendly aluminum sol coating includes the following steps:

[0075] S1. Substrate pretreatment:

[0076] After degreasing with acetone and rinsing with deionized water, the 6061 aluminum alloy plate (5cm×5cm×0.2cm) is immersed in the pretreatment working solution and soaked at room temperature for 8 minutes. After being taken out, it is dried at 70℃ for 6.5 minutes to form a catalytically active transition layer on the substrate surface.

[0077] The pretreatment working solution is prepared by dissolving 1.0 g / L of tannic acid in deionized water and adding 0.20 g / L of FeCl3·6H2O (tannic acid: Fe...). 3+ The molar ratio of the two compounds was 3.4:1, and the mixture was stirred to form a purple coordination complex. Then, 2.5 g / L KH550 was added and hydrolyzed for 10 min. 0.15 g / L D80 was added and stirred for 5 min. The pH was adjusted to 5.2 with 0.1 mol / L dilute hydrochloric acid and aged for 20 min.

[0078] The pretreated substrate should be coated within 1 hour to avoid secondary contamination.

[0079] S2. Preparation of basic sol:

[0080] Dissolve 0.5 parts of polyvinyl alcohol and 0.2 parts of polyethylene glycol in 26 parts of deionized water, stir at 90°C until completely dissolved, cool to room temperature, and then add 10 parts of anhydrous ethanol, 15 parts of neutral aluminum sol (solid content of 20%, pH value of 5.2) and 3.0 parts of methyltrimethoxysilane in sequence, and stir at room temperature to obtain the basic sol.

[0081] S3, Addition of catalytic and antibacterial components:

[0082] Add 2.0 parts of tannic acid (10wt%) (containing 0.20 parts of tannic acid) to the base sol at a rate of 1.5 mL / min while stirring at a medium speed of 400 rpm. After the addition is complete, add 0.10 parts of dibutyltin dilaurate and 0.10 parts of ε-polylysine (molecular weight 4000). Stir at room temperature until homogeneous to obtain a composite sol. Maintain the pH of the system at 5.2.

[0083] S4. Aging and Coating:

[0084] After aging the composite sol for 2 hours, it was coated onto the surface of the pretreated aluminum alloy plate using a dip-coating method (speed 15 cm / min), with a wet film thickness of 25 μm.

[0085] S5, Two-step gradient thermosetting:

[0086] The first stage involves curing at a constant temperature of 100℃ for 1 hour.

[0087] The second stage involves curing at a constant temperature of 120℃ for 0.5 hours.

[0088] No ultraviolet light exposure throughout the process to avoid photo-induced hydrophilic conversion;

[0089] S6. Post-processing:

[0090] A zinc ion-containing precursor solution is sprayed onto the cured coating surface. The phenolic hydroxyl groups of tannic acid in the coating are used to anchor the zinc ions in situ. After drying at 75°C for 18 minutes, zinc oxide nanoparticles are generated in situ on the coating surface, forming a photocatalytic self-cleaning functional layer.

[0091] The zinc ions in the precursor solution are derived from zinc acetate, with a zinc ion concentration of 0.15 mol / L. The solvent is a water-ethanol mixture (ethanol:water = 1:2, v / v), and the solution pH is 6.2.

[0092] The zinc ion spraying amount is 0.35 mg Zn / cm³. 2After spraying, let it stand at room temperature for 9 minutes before drying.

[0093] Example 3

[0094] A method for preparing a high-performance, environmentally friendly aluminum sol coating includes the following steps:

[0095] S1. Substrate pretreatment:

[0096] After degreasing with acetone and rinsing with deionized water, the 6061 aluminum alloy plate (5cm×5cm×0.2cm) is immersed in the pretreatment working solution and soaked at room temperature for 10 minutes. After being taken out, it is dried at 80℃ for 5 minutes to form a catalytically active transition layer on the surface of the substrate.

[0097] The pretreatment working solution is prepared by dissolving 1.2 g / L of tannic acid in deionized water and adding 0.32 g / L of Fe(NO3)3·9H2O (tannic acid: Fe 3+ The molar ratio of the two compounds was 3.8:1, and the mixture was stirred to form a purple coordination complex. Then, 3.0 g / L of KH550 was added and hydrolyzed for 10 min. 0.20 g / L of D80 was added and stirred for 5 min. The pH was adjusted to 5.5 with 0.1 mol / L dilute hydrochloric acid and aged for 30 min.

[0098] The pretreated substrate should be coated within 1 hour to avoid secondary contamination.

[0099] S2. Preparation of basic sol:

[0100] Dissolve 0.6 parts of polyvinyl alcohol and 0.25 parts of polyethylene glycol in 27 parts of deionized water, stir at 90°C until completely dissolved, cool to room temperature, and then add 11 parts of anhydrous ethanol, 15 parts of neutral aluminum sol (solid content of 20%, pH value of 5.5) and 3.2 parts of methyltrimethoxysilane in sequence, and stir at room temperature to obtain the basic sol.

[0101] S3, Addition of catalytic and antibacterial components:

[0102] Add 2.5 parts of tannic acid (10wt%) (containing 0.25 parts of tannic acid) to the base sol at a rate of 2 mL / min while stirring at a medium speed of 500 rpm. After the addition is complete, add 0.12 parts of dibutyltin dilaurate and 0.15 parts of ε-polylysine. Stir at room temperature until homogeneous to obtain a composite sol. Maintain the pH of the system at 5.5.

[0103] S4. Aging and Coating:

[0104] After aging the composite sol for 2 hours, it was coated onto the surface of the pretreated aluminum alloy plate using a dip coating method (speed 20 cm / min), with a wet film thickness of 30 μm.

[0105] S5, Two-step gradient thermosetting:

[0106] The first stage involves curing at a constant temperature of 105℃ for 0.8 hours.

[0107] The second stage involves curing at a constant temperature of 125℃ for 0.4 hours.

[0108] No ultraviolet light exposure throughout the process to avoid photo-induced hydrophilic conversion;

[0109] S6. Post-processing:

[0110] A zinc ion-containing precursor solution is sprayed onto the cured coating surface. The phenolic hydroxyl groups of tannic acid in the coating are used to anchor the zinc ions in situ. After drying at 80°C for 15 minutes, zinc oxide nanoparticles are generated in situ on the coating surface, forming a photocatalytic self-cleaning functional layer.

[0111] The zinc ions in the precursor solution are derived from zinc acetate, with a zinc ion concentration of 0.20 mol / L. The solvent is a water-ethanol mixture (ethanol:water = 1:3, v / v), and the solution pH is 6.5.

[0112] The amount of zinc ions sprayed is 0.4 mg Zn / cm³. 2 After spraying, let it stand at room temperature for 10 minutes before drying.

[0113] Comparative Example 1

[0114] Compared with Example 2, Comparative Example 1 only involves degreasing and cleaning of the substrate in step S1, step S5 uses one-step constant temperature curing (120℃×1.5h), and there is no post-treatment step S6. The remaining steps and parameters are the same as in Example 2.

[0115] Comparative Example 2

[0116] Compared to Example 2, this comparative example used conventional silane pretreatment (only 2.5 g / L KH550, pH=5.2, no TA / Fe). 3+ / D80), and there is no post-processing step S6, the remaining steps and parameters are the same as in Example 2.

[0117] Comparative Example 3

[0118] Compared with Example 2, Comparative Example 3 does not add D80 in step S3, while the other steps and parameters are the same as in Example 2.

[0119] Comparative Example 4

[0120] Compared with Example 2, Comparative Example 4 does not add ε-polylysine in step S3, while the other steps and parameters are the same as in Example 2.

[0121] 1. Experimental testing

[0122] 1.1 Adhesion Test (Cross-cut Adhesion Test)

[0123] According to GB / T 9286-1998, use a cross-cutting tool (1mm spacing) to draw 10×10 squares on the coating surface, attach 3M tape vertically and then quickly peel it off, observe the peeling area, and rate it from 0B to 5B.

[0124] 1.2 Contact Angle Test

[0125] Using an OCA20 contact angle meter, 2 μL of ultrapure water was added at room temperature, and the average value was taken at 5 different locations for each sample.

[0126] 1.3 Thermogravimetric analysis (TGA)

[0127] The HTG-4 thermogravimetric analyzer was used under a nitrogen atmosphere at a heating rate of 10℃ / min to raise the temperature from room temperature to 800℃. The initial decomposition temperature (Td, 5%, the temperature at which the mass loss is 5%) and the char residue at 800℃ were recorded.

[0128] 1.4 Antibacterial performance test

[0129] According to GB / T 21866-2008, the inhibition rate against *Escherichia coli* and *Staphylococcus aureus* was tested using the film-applied method. The sample size was 50 mm × 50 mm, and the inoculum concentration was 1 × 10⁻⁶. 5 CFU / mL, the inhibition rate was calculated after 24 hours of contact.

[0130] 1.5 Self-cleaning performance (photocatalytic degradation)

[0131] Using methylene blue (MB) as the target pollutant, samples (2cm × 2cm) coated with ZnO were placed in 10mL of 10mg / L MB solution and irradiated under a UV lamp (365nm, 10W) ​​for 2h. The degradation rate was measured using a UV-Vis spectrophotometer. This step was not performed on samples without post-treatment.

[0132] 1.6 Salt spray resistance test

[0133] According to GB / T 10125-2021, neutral salt spray test (NSS), 5 wt% NaCl solution, 35 ℃, continuous spraying for 500h, observe the percentage of corrosion area on the coating surface.

[0134] 2. Experimental Results and Analysis

[0135] 2.1 Basic Performance

[0136] Table 3. Basic properties of the coatings in each embodiment and comparative example.

[0137] Example 1 4B 105.2 275 38.2 73.5 Example 2 5B 118.6 298 45.6 84.2 Example 3 4B 112.3 289 42.8 80.1 Comparative Example 1 2B 87.3 235 22.1 — Comparative Example 2 3B 95.2 250 28.3 — Comparative Example 3 3B 102.5 268 33.6 82.5 Comparative Example 4 5B 117.2 295 44.8 83.8

[0138] Note: "—" indicates that no ZnO post-treatment was performed, therefore the MB degradation rate was not measured.

[0139] As shown in Table 3 above, regarding adhesion: Example 2 achieved the highest grade of 5B, with no peeling observed in the cross-cut adhesion test; Examples 1 and 3 were 4B; Comparative Example 1 was only 2B; Comparative Example 2 was 3B; Comparative Example 3 was 3B; and Comparative Example 4 remained at 5B, indicating that ε-PL does not affect adhesion. The improved adhesion is attributed to the tannic acid-Fe in the pretreatment layer. 3+ The strong anchoring of the coordination network to the substrate and the D80-catalyzed interfacial covalent cross-linking further reduce internal stress through two-step gradient curing.

[0140] Contact angle: Example 2 showed the highest contact angle, exhibiting a typical hydrophobic / superhydrophobic state; Examples 3 and 1 showed the next highest; and Comparative Example 1 showed the lowest. The increased contact angle is attributed to the formation of micro-nano rough structures through PEG-induced microphase separation during the two-step gradient curing process, as well as the low surface energy Si-CH3 groups provided by MTMS. Comparative Example 1 failed to form a rough structure during one-step curing, Comparative Example 2 showed insufficient surface roughness after conventional silane treatment, and Comparative Example 3 lacked D80, resulting in insufficient crosslinking and an incomplete rough structure.

[0141] Thermal stability: Example 2 showed the best Td (5%) and char residue; Example 3 was slightly lower; Example 1 was next; Comparative Example 1 was the worst. This indicates that tannic acid-Fe... 3+ The catalytic effect of the network and D80, together with the D80 of the coating body and gradient curing, construct a highly cross-linked interpenetrating network, which significantly improves the thermal decomposition temperature and char formation rate.

[0142] Photocatalytic self-cleaning (MB degradation rate): Only samples post-treated with ZnO showed degradation ability. Example 2 had the highest rate, followed by Example 3 and Example 1. Although Comparative Example 3 had post-treatment, its coating cross-linking was slightly worse, but the degradation rate of 82.5% was still relatively high, indicating that ZnO formation mainly depends on tannic acid anchoring and has no direct conflict with D80.

[0143] 2.2 Antibacterial properties

[0144] Test results are as follows Figure 1 As shown. By Figure 1 It was found that all samples with added ε-polylysine (Examples 1-3, Comparative Examples 1-3) exhibited an inhibition rate of ≥95% against both bacteria, with Example 2 showing the highest inhibition rate (>99%). ε-polylysine is a broad-spectrum, highly effective natural antibacterial agent, and its antibacterial activity is unaffected by pretreatment methods, the presence or absence of D80, or curing processes (Comparative Examples 1-3 maintained high inhibition rates). Comparative Example 4 showed an extremely low inhibition rate, and this residual activity stemmed from the weak antibacterial properties of tannic acid itself. Therefore, the highly effective antibacterial function in this invention relies entirely on the addition of ε-polylysine, and this component has no antagonistic effect with other components in the system.

[0145] 2.3 Salt spray resistance

[0146] Test results are as follows Figure 2 As shown. By Figure 2 It can be seen that Example 2 has the smallest corrosion area and the best performance; Examples 3 and 1 are slightly worse in that order; Comparative Example 1 has the most severe corrosion due to lack of pretreatment, poor adhesion, and an unstable coating; Comparative Example 2, although treated with conventional silane, lacks a coordination network and catalytic crosslinking; Comparative Example 3, due to the lack of D80 in the coating body and insufficient crosslinking, shows a significant increase in corrosion; Comparative Example 4 is similar to Example 2, proving that ε-PL has no negative impact on corrosion resistance. The results show that the present invention comprehensively employs a biomimetic coordination catalytic transition layer, dual-source D80 catalysis, gradient curing, and ε-PL antibacterial properties, synergistically endowing the coating with excellent salt spray corrosion resistance.

[0147] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing a high-performance, environmentally friendly aluminum sol coating, characterized in that, Includes the following steps: S1. Substrate pretreatment: The degreased and cleaned substrate is immersed in the pretreatment working solution at room temperature, then removed and dried to form a catalytically active transition layer on the substrate surface. S2. Preparation of basic sol: Polyvinyl alcohol and polyethylene glycol were dissolved in deionized water and stirred at 90°C until completely dissolved. After cooling to room temperature, anhydrous ethanol, neutral aluminum sol, and methyltrimethoxysilane were added in sequence and stirred at room temperature to obtain the basic sol. S3, Addition of catalytic and antibacterial components: Add tannic acid to the base sol, controlling the addition rate to ≤2mL / min, while stirring at medium speed. After the addition is complete, add dibutyltin dilaurate and ε-polylysine, and stir evenly at room temperature to obtain a composite sol. Maintain the pH of the system at 5.0~5.

5. S4. Aging and Coating: The composite sol is aged and then coated onto the surface of the pretreated substrate. The wet film thickness is 20~30μm; S5, Two-step gradient thermosetting: The thermosetting process is carried out in two stages.

2. The preparation method according to claim 1, characterized in that, Raw materials by weight: 15 parts neutral aluminum sol, 2.8-3.2 parts methyltrimethoxysilane, 0.4-0.6 parts polyvinyl alcohol, 0.15-0.25 parts polyethylene glycol, 0.15-0.25 parts tannic acid, 0.08-0.12 parts dibutyltin dilaurate, 0.05-0.15 parts ε-polylysine, 9-11 parts anhydrous ethanol, and 25-27 parts deionized water.

3. The preparation method according to claim 1, characterized in that, It also includes S6, post-treatment: a zinc ion-containing precursor solution is sprayed onto the cured coating surface, and the zinc ions are anchored in situ by the coordination of the phenolic hydroxyl groups of tannic acid in the coating. After drying at 70~80℃ for 15~20min, zinc oxide nanoparticles are generated in situ on the coating surface, forming a photocatalytic self-cleaning functional layer.

4. The preparation method according to claim 3, characterized in that, The zinc ions in the precursor solution are derived from zinc acetate or zinc nitrate, with a zinc ion concentration of 0.10~0.20 mol / L, and the solvent is a water-ethanol mixture with a solution pH of 6.0~6.

5.

5. The preparation method according to claim 3, characterized in that, The amount of zinc ions sprayed is 0.3~0.4 mg Zn / cm³. 2 After spraying, let it stand at room temperature for 8-10 minutes before drying.

6. The preparation method according to claim 1, characterized in that, The preparation of the pretreatment working solution in step S1 includes the following steps: (1) Dissolve tannic acid in deionized water and add Fe 3+ Salt, stir for 1-2 minutes to form a purple coordination complex; (2) Add γ-aminopropyltriethoxysilane and hydrolyze for 10 min; add dibutyltin dilaurate and stir for 5 min; (3) Adjust the pH to 5.0~5.5 and age for 15~30 minutes.

7. The preparation method according to claim 1, characterized in that, The neutral aluminum sol described in step S2 has a solid content of 20% and a pH value of 5.0~5.

5.

8. The preparation method according to claim 1, characterized in that, The thermosetting treatment in step S5 specifically includes: The first stage involves constant temperature curing at 95~105℃ for 0.8~1.2 hours; The second stage involves constant temperature curing at 115~125℃ for 0.4~0.6 hours; There is no ultraviolet light exposure throughout the process to avoid photo-induced hydrophilic transformation.

9. An aluminum sol coating prepared by the method according to any one of claims 1 to 8.

10. The application of the aluminum sol coating of claim 9 in self-cleaning glass for buildings, dustproofing for photovoltaic panels, automotive coatings, anti-corrosion for ships, antibacterial protection for medical devices, or moisture protection for electronic components.